Projections of Brazilian biomes resilience and socio-environmental risks to climate change - Pinho, Patrícia F.; Anjos, Luciano J. S.; Rodrigues-Filho, Saulo; Santos , Diogo V.; Toledo, Peter M. (Sustainability in Debate, 2020)
Climate change has been considered, at a global level, as one of the main anthropogenic drivers of environmental transformation, especially on biomes, ecosystems and the most vulnerable population. In this regard, the concept of resilience has been widely used in ecology to explain the ecosystem transition thresholds by which forests and other habitats are able to restructure in the face of various external disturbances. However, the concept of resilience in facing climate change impacts and risks through the lens of socio-environmental risks in Brazil is still underdeveloped, especially at the biome level. This article uses the theory of critical transitions to ecological niche distribution modeling in future global warming scenarios by the end of the century, in order to highlight the change in ecological resilience of the Amazon, Caatinga, Cerrado, Atlantic Forest and Pampa biomes, and how the changes in resilience can lead to an increased exposure, vulnerabilities and risks to socio-environmental security. This article shows how an interdisciplinary approach bringing together modeling of biome resilience may be a tool to support decision making and public policies on mitigation and adaptation to climate change and reduce risks to socio-environmental security.